Effect of gamma irradiation of seeds on the development of Phaseolus vulgaris L. plants - O. A. Kotsyubinskaya; E. V. Bondarenko; N. G. Kazydub; Ya. A. Blinova (Овощи России, 2025)
Relevance. The modern direction of bean breeding is focused on increasing the protein content in seeds and green beans, as well as vitamins, folic acid, biologically active substances and antioxidants, improving organoleptic properties and reducing the content of anti-nutritional substances. When creating the initial material for breeding, the following traits are important: resistance to biotic and abiotic factors, stable high yield, technological effectiveness, bush type and upright form, high symbiotic activity. An effective approach to increasing the genetic diversity of the initial material is radiation mutagenesis.Purpose of research. To study the effect of γ-irradiation of seeds on germination, morphometric parameters and duration of phenophases of Russian bean varieties and to determine the optimal dose of γ-radiation for the radiation mutagenesis protocol.Materials and Methods. Objects of the study – 3 bean varieties bred by Omsk State Agrarian University. The seeds were γ-irradiated (source – 60Co) at doses of 50–200 Gy (dose rate 60 Gy/hour). The seeds were germinated under controlled conditions; germination energy and germination were assessed. The hypocotyl length, number and length of roots were measured in seedlings. The duration of development phases and productivity of plants were assessed. Statistical analysis was performed in R (ver. 4.3.3) and MS Office Excel 2019.Results. Hormesis effect was noted for 50 Gy γ-irradiation dose, which was manifested in higher values of germination energy and seed germination (variety Pamyati Ryzhkova), hypocotyl length (variety Marusya and Pamyati Ryzhkova) and in a decrease in the phenophases duration (variety Omskiy Rubin). Gamma irradiation at all applicable doses statistically significantly inhibited root development. Root length, as the most sensitive parameter to radiation, was chosen to calculate the dose causing a 50% growth reduction (RD50). For the Marusya variety, RD50 was 40 Gy, for the Pamyati Ryzhkova and Omsky Rubin varieties - 60 Gy.Conclusion. Variety specificity was established in the reaction to seed irradiation. Doses of 50 Gy or less (10-50 Gy) can be used to study the hormetic effects of γ-irradiation of bean seeds. Doses of 100 and 200 Gy turned out to be lethal. Starting doses of 40-60 Gy are recommended for the radiation mutagenesis protocols of Russian bean varieties.